Impact of an improved outdoor space on people with dementia in a hospital unit - Ng, Lorraine; Dyer, Suzanne M.; Dawson, Suzanne; Laver, Kate (Frontiers in Dementia, 2024)
Introduction Gardens and outdoor spaces are an important part of institutional environments for people with dementia. However, evidence regarding the benefits these spaces have for people with dementia is still limited. This paper presents the evaluation of the redevelopment of an inaccessible outdoor space into a therapeutic garden on a high dependency psychogeriatric unit in an acute hospital. Method A Mixed methods evaluation was undertaken. An interrupted time series analysis investigated the impact of the garden on falls and challenging behaviours of patients using routinely collected data. Perspectives of the redeveloped garden were captured through (a) a staff survey and (b) semi-structured interviews with families of patients. Results Rates of falls and challenging behaviours dropped at the time of the garden opening but showed increasing rates each month both before and after the garden opened. Most staff believed that the garden provided benefits for patients however limited staff time and concerns over patient safety were barriers to use. Families identified four main themes related to garden use including: 1) being outside 2) occupation and identity, 3) being stimulating and 4) barriers and facilitators. Conclusion The garden was regarded positively by families and staff however, there were barriers that prevented it from being better utilised. Staff concerns over risk were not reflected in falls and challenging behaviour outcomes. Further research into how barriers to garden use may be overcome is justified.